Automated Bus Crew Rescheduling for Late for Sign-On (LFSO) Event using Multi-Agent System - Shibghatullah, A.S.; Safei, S.; Abal Abas, Z.; Zainal Abidin, Z.; Musa, H.; Rahmalan, H. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
Unpredictable events (UE) are major factors that cause crew rescheduling to be performed. One of the UE is when a crew is late for duty. In this research, it is termed as Late for Sign-On (LFSO). When LFSO occurred, the reschedule is needed to make sure available crew take the duty. Currently, there is no automated mechanism to handle the LFSO. Real time rescheduling approaches mostly are not supported due to static schedules constraint. Mathematical approaches require extensive computational power therefore delayed the real-time results. Meanwhile, manual rescheduling is prone to error and not optimum. This research objective is to develop a new approach in automating the crew rescheduling process using multiagent system. The agents dynamically adapt their behaviour to changing environments quickly and find solutions via negotiations and cooperation between them. Experiment is conducted using AgentPower simulation tool. The result concluded that the proposed technique is capable to reschedule quickly. The distribution of a duty also plays a major role in achieving rescheduling success.